Democracy, state and capital: the `unthought' of 20th century Marxism - Nigam, Aditya (2009)
Is democracy in India a sham, as the Maoists and indeed many other leftists claim? If so, how do we understand the experience of many oppressed groups who have found this democracy enabling in many ways? A possible way out of this endless debate is to see democracy not as a fully-formed end product of liberal-constitutionalism but as its untamed other - the mass politics which escapes and exceeds the Law and the injustices of Order. it is from here that the greatest challenges to capitalism and the State arise. The Maoist strategy, be merely trying to mimic the State, is actually inimical to this democratic upsurge and therefore needs to be resisted. (Reproduced).
Keywords: Marxism - 20th Century; Marxism